Cross-market correlations and financial contagion from developed to emerging economies: A case of COVID-19 pandemic - Taufeeque Ahmad Siddiqui; Mazia Fatima Khan; Mohammad Naushad; Abdul Malik Syed (Economies, 2022)
In the event that the COVID-19 pandemic spreads across various stock markets, this study may be deemed as one of the primary studies to evaluate cross-market interactions. The study examines the spread of contagious effects originating from developed economies (the United States, the United Kingdom, and Japan) to selected emerging markets (China, India, Thailand, Taiwan, Egypt, South Africa, Saudi Arabia, and the United Arab Emirates). The countries studied are classified into three regions: developed economies, Asia, and Africa and the Middle East. The crisis period is identified with the deployment of the Markov regime-switching model. The conditional correlations are compared before and after the crisis episode using the time-varying multivariate DCC-GARCH model. The findings confirm that certain emerging markets are experiencing contagion from developed markets, while others remain unaffected. Overall, investors in the two regions examined (Asia, and Africa and the Middle East) have comparable diversification options. The findings are expected to bolster policymakers and international agencies in developing post-crisis measures.
Keywords: G11; G12; G13; G15; G17; 330; co-movement; COVID-19; DCC-GARCH; financial contagion; stock markets